PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA STUDIO FOTO SETIA JAYA DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI KECAMATAN SUBOH KABUPATEN SITUBONDO - Agusta, Kuku; Karnadi, Karnadi; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of service quality on consumer loyalty at Setia Jaya Photo Studio with Consumer Satisfaction as an Intervening Variable in Suboh District, Situbondo Regency. The sampling technique used in this study is probability sampling with a simple random sampling technique with the Slovin formula with a tolerable error rate of 10% as many as 91 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that service quality has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on consumer loyalty, consumer satisfaction has a positive and significant effect on consumer loyalty, service quality has a positive but not significant effect to consumer loyalty through consumer satisfaction.